EVIDENCE BASED CASE REPORT (EBCR) : PENGARUH MUROTAL AL-QURAN TERHADAP TINGKAT KECEMASAN PADA IBU BERSALIN (Jurnal Kesehatan Siliwangi, 2022)
Background: Labor or delivery is a physiological condition that usually occurs in a woman's life. Maternity events are one of the important moments for mothers, especially mothers who are giving birth for the first time. Maternal labor is generally followed by an emotional transition characterized by mood swings, anxiety, and sadness as well as the effects of dizziness and nausea. Purpose: To determine whether murotal al-quran has an effect on reducing anxiety in pregnant women. Methods: The research was conducted through literature searches in several articles, namely Google Scoolar and Garuda. Results: There were 20 people who experienced a decrease in anxiety from before the intervention by giving Murottal Al Quran.There was an emotional effect on maternal anxiety from the murottal Al-Quran treatment. Conclusion: Listening to the murotal al-quran is proven to reduce anxiety when mothers give birth, murotal al-quran is able to reduce anxiety in mothers in childbirth.